IDENTIFIKASI MODEL MENTAL MAHASISWA PADA KONSEP ATOM BERELEKTRON TUNGGAL - Hermawan, Dian Wahid; Yulianto, Agus (Universitas Negeri Semarang, 2017)
Most of physics students hold classical physics perspective when they learn quantum physics. Modeling instruction is implemented to identify mental models changing in learning quantum conceptual models. Mental model is an image created in the mind of a natural phenomenon. The conceptual model is a description of natural phenomena in appropriate with the scientists perspective. Qualitative analysis used in this research is grounded theory. The results of identification student model mental is categorized as quantum, intermediate and clasical mechanics. Students have experienced changing of dimensional understanding area from classical mechanics into a quantum perpective. The accuracy of mental model identification can be improved by making the interpretation image repeatedly.